Using web-based simulated classroom to develop pre-service teachers’ classroom assessment practice - Wei Wei, Rong Xia, Haoming Lin, Ziqi Chen, Xiaoshu Xu (Educational Technology & Society)
The development of classroom-based formative assessment is crucial for preservice teachers. This study investigated the extent to which Virtual Reality (VR) simulation may improve teacher trainees’ self-efficacy and influence their preferences regarding classroom-based formative assessment practices. A total of 66 pre-service language teacher trainees from one of the largest teacher training centers in East China participated in the study. Random assignment was used, with half of the participants assigned to the experimental group and the other half to the control group. The quasi-experimental study revealed that teacher trainees in the VR experimental group reported significantly higher self-efficacy levels in designing and operating classroom-based formative assessment tasks. Additionally, they expressed stronger preferences for using such tasks in the post-test, compared to their pre-test ratings. In contrast, no significant difference was observed between the two tests in the control group. Furthermore, Analysis of Covariance (ANCOVA) test results confirmed this pattern even after controlling for teacher trainees’ pre-test ratings. These findings underscore the considerable potential of using VR-simulated activities as an effective means to enhance teacher assessment literacy and practice.